Estudo do comportamento à fadiga de misturas cimentadas do tipo BGTC utilizando duas rochas extrusivas representativas do estado do RS - Back, Ana Helena (2022)
The densification of the road sector makes it necessary to enable structures with higher structural capacity, one of the developed technics is the insertion of cemented layers. Regarding the use of cement treated crushed stones as an alternative for cemented material, the state of art and the state of practice point out certain limitations regarding to the fragile rupture process due fatigue, promoting accelerated damage to pavement structures, however, there are few academic productions that aim to elucidate the behavior of these materials towards the main rupture mechanism. Thus, this research aims to study the fatigue behavior by indirect tensile test method of four cement treated crushed stones mixtures, aiming the development of their fatigue models. In addition, laboratory tests were carried out to determine the strength properties (Axial, Flexural, ITS), stiffness (RM and EM), as well as performance indicators (toughness index and fracture energy), using software adapted to the ITS test. The selection of materials for the cement treated crushed stones composition occurred due the expressive representativeness within the state of RS, so that the mixtures were compounded by two igneous extrusive rocks (basalt and rhyodacite), Portland Pozzolanic cement CP IV 32-RS, cement contents of 3,5% and 5,5%, curing ages of 28, 91 and 120 days and “B” grain size distribution (NBR 11803/2003). Analyzes of significant association were performed between the laboratory tests and the adopted parameters (cement content, curing age and rock types), in addition, the software MeDiNa was used to develop a mechanistic analysis by different configurations of semi-rigid and inverted semi-rigid pavements to replace the granular layers of a flexible pavement, taken as a reference. From the obtained results in accordance with the methodological outline, it is identified that: a) the increase of cement content and curing age promoted an improvement in the strength and stiffness parameters for all analyzed tests; b) The origin characteristics of rocky materials reflected in the parameters of the cement treated crushed stones, however, having a higher density was not an absolute guarantee of better mechanical behavior; c) Regarding the mechanistic analysis, it is concluded that cemented mixtures with higher cement content are effective for both base and sub-base layers, as long as the cemented layers are not thin; d) A fine line is identified between cost and laboratory performance, not only for the Axial test, which, although showing extreme notoriety as a dosage parameter, exhibits limitation for evaluating the main failure mode of such materials, fatigue cracking.